Solve -4*y + 4*o + 24 = 0, 0 = -9*o + 4*o - 20 for y.
2
Solve -3*t - 10 = x, -3*t = t - 4*x + 8 for t.
-3
Solve -d + n + 5 = -0*n, -5*n - 25 = -3*d for d.
0
Solve -5*a - 11 = 4*o, o - 4*a - 12 - 1 = 0 for o.
1
Solve -5*t = p + 4*p + 5, -t + 4*p - 6 = 0 for t.
-2
Solve -3*u = 3*p - 9, -4*p - 6 = u - 6*u for u.
2
Solve 2*m - 4 = 0, -40*z = -38*z + 5*m - 2 for z.
-4
Solve -5*d + 4*o = -6*d - 17, -2*d = 4*o + 18 for d.
-1
Solve -4*p + 2*t = 4, -p - 3*t = -t + 11 for p.
-3
Solve -3*m = 4*k + 2, -3 + 7 = -2*k for m.
2